2013
DOI: 10.1002/bmc.2957
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of automated SPE‐LC‐MS/MS method for determination of indapamide in human whole blood and its application to real study samples

Abstract: A fast and simple liquid chromatography-electrospray ionization tandem mass spectrometry method for determination of indapamide in human whole blood was developed and validated. The sample extraction of indapamide from human whole blood was achieved using automated solid-phase extraction. Chromatographic separation was performed on Kinetex C18 column (100 × 2.1 mm, 1.7 µm particle size) using acetonitrile and 2 mm ammonium formate in ratio 90:10 (v/v) as a mobile phase. The mass spectrometer was operated in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 9 publications
0
10
0
Order By: Relevance
“…Three freeze-thaw cycles, long-term storage at − 80 °C for one month and short-term stability of the biological samples did not result in obvious changes in the drug concentration, as earlier publications have reported [9] , [10] , [11] , [12] , [13] , [14] , [18] . And the stability results of analytes after 30 h in autosampler at 8 °C were within 85%–115% of the actual concentration ( Tables S9 and S10 ).…”
Section: Resultsmentioning
confidence: 52%
See 1 more Smart Citation
“…Three freeze-thaw cycles, long-term storage at − 80 °C for one month and short-term stability of the biological samples did not result in obvious changes in the drug concentration, as earlier publications have reported [9] , [10] , [11] , [12] , [13] , [14] , [18] . And the stability results of analytes after 30 h in autosampler at 8 °C were within 85%–115% of the actual concentration ( Tables S9 and S10 ).…”
Section: Resultsmentioning
confidence: 52%
“…C max and AUC 0-t showed significant differences between plasma and whole blood for all three analytes. For indapamide, due to the high binding to the red blood cell [18] , [19] the C max and AUC 0-t in whole blood were higher than those in plasma while it presented an opposite result for perindopril and perindoprilat. As per the literature [20] , perindopril and perindoprilat bind mainly to plasma protein in blood, which resulted in the lower concentration levels in whole blood.…”
Section: Resultsmentioning
confidence: 86%
“…The existing literature data have shown that the use of fully-porous particles (Chen et al, 2006;Ding et al, 2006 andMorihisa et al, 2008) or monolithic columns (Albu et al, 2005) did not provide separation of indapamide within short runtime. In our previous work, method for determination of indapamide in human whole blood using core-shell stationary phase was developed (Nakov et al, 2013). These particles are not fully porous; analytes spend less time diffusing into and out of the pores, resulting in faster mass transfer and shorter run time.…”
Section: Methods Developmentmentioning
confidence: 99%
“…The possibility of lysis of the erythrocytes makes its determination from blood more appropriate and precise. There are number reports concerning determination of indapamide in whole blood using high-performance liquid chromatography with ultraviolet detection (HPLC-UV) and liquid chromatography coupled with mass spectrometry (LC-MS) (Miller et al, 1993;Zendelovska et al, 2003;Tang et al, 2005;Hang et al, 2006;Jain et al, 2006;Nakov et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation